El Kamari ista de Canelos: función y significado del gran ritual amazónico - Cabrero, Ferran (2023)
The largest Kamari ista (banquet or festival of abundance) in the entire Kichwa-speaking Amazon is celebrated in the community and rural parish of Canelos, in the Pastaza district in the province of the same name, in Ecuador. Based on a request from the same community for the Kamari to be registered and certified as national heritage, between 2013 and 2022 participatory ethnographic work was carried out to prepare the base document for said goal. In this process, it became evident that, beyond certainethnographic works from several decades ago, little is known today about this festival or ritual, its function and meaning. Starting from the work carried out within the framework of heritage certification, the objective of this article is to analyse the Kamari of Canelos from an anthropological perspective: its complex process of preparation and development, its intercultural origin, and especially its social function and cultural meaning.